Information Technology Innovation and Organizational Policy - Joseph, Bengat K.; R. J 2, Tubey; Rotich3, Jacob K (My University, 2015)
Issues relating to workplace privacy and how organizations address privacy have sparked a lot of public debate in recent years. Research reveals that potential employers have exploited employees seeking job opportunities by asking information to do with: disclosure of confidential information about the past employer’s work, financial background, and family intimate issues not relevant to the job being sought among others. This paper establishes the implications of information technology innovation on organization policies with emphasis on employees’ privacy. The study was done in two organizations and it adapted a case study approach. Data was collected from 74 respondents using questionnaires. Respondents were sampled using purposive technique. Frequency distribution tables were used in data presentation followed by discussions. The findings of this study are critical in informing the policy makers in organizations on procedures and strategies of inclusive policy formulation and implementation as well as provide HR managers with insight on managing privacy issues in dynamic organizational setups
Implications on Employee Privacy
Keywords: Employees’ Privacy policy; Information Technology; Surveillance